(untitled) (Vietnam Journal of Community Medicine, 2024)
Objective: Determining the rate of overweight, obesity, and factors related to this condition among students of the University of Medicine and Pharmacy at Ho Chi Minh City (UMP). Methods: A cross-sectional study was conducted from February to May 2024 among students of the UMP based on the structured questionnaire including anthropometric index (height, weight), personal and family. Results: Students with overweight, and obesity were 41,7%; in which the rate of overweight is 23,4% and obesity is 18,3%. Factors with a statistically significant relationship (p<0,05) between overweight, and obesity included: Gender, people living with, average amount of filtered water consumed per day, monthly food expenditure, family and friends with overweight - obesity, academic performance, eating out with friends and the amount of carbonated soft drinks consumed each time. Conclusion: The rate of overweight and obesity, and the consumption of sugary drinks among students is relatively high. The measures are needed to help students limit their use of sugary drinks and improve their nutritional status and health.